Why testify?: Witnesses’ motivations for giving evidence in a war crimes tribunal in Sierra Leone - Stepakoff, Shanee (International journal of transitional justice, 2014)
Although witnesses are indispensable to the operation and success of war crimes courts, little is known about their motivations for agreeing to testify. This article advances existing knowledge by drawing on findings from interviews conducted with 200 witnesses after they gave evidence in the Special Court for Sierra Leone. Participants were asked to describe their reasons for testifying. Content analysis was used to examine the variety and frequency of responses. Overall, 18 conceptually distinct motivations were mentioned, with most witnesses reporting multiple motivations. The response given most frequently was ‘to denounce wrongs committed against me during the war,’ followed by ‘to contribute to public knowledge about the war.’ Desires for retributive justice (e.g., accountability, punishment), and to fulfill a moral duty to other victims, were each mentioned by approximately one in four witnesses. Other key motivations included establishing the truth and narrating their stories. Motivations differed by gender, age, victimization status, side (prosecution versus defense) and trial. The results support the idea that witnesses value the opportunity to publicly denounce atrocities committed against themselves and others. The findings point to both congruities and incongruities between the aims of witnesses and the goals of war crimes courts. Further, the findings suggest that there may be two broad, overarching aspects of the decision to testify: those that are primarily geared toward helping oneself and those that are primarily geared toward helping others. Pragmatically, the findings can enhance efforts to support witnesses in preparing for and completing their testimonies.